Inovasi Financial Technology (Fintech) pada Asuransi Syariah (Studi kasus: PT Duta Danadyakasa Teknologi) - Indri Nuranggraeni (JESI (Jurnal Ekonomi Syariah Indonesia), 2019)
This study aims to identify problems, solutions and strategies in decision making of fintech innovation insurance, with the approach method is Analytic Network Process (ANP). The data collections which are depth interview and questionnaire were collected from the respondent. The results showed that the priority issues faced in fintech innovation insurance are human aspect which consists of human resource lacks and regulatory challenges; product aspect which consists of product penetration and asset market penetration fractional shari’ah. Solutions which are needed in fintech innovation insurance are aspect human which consists of resource and regulation minimalism; product aspect which consists of product research and product innovation. Strategies in fintech innovation insurance are socialization, education, cooperation and digital marketing. Socialization gives the most influence on fintech innovation insurance to introduce fintech in facing digital era. Education needs to be held periodically as well as in the process of fintech to get the assistance of the Otoritas Jasa Keuangan (OJK) as a regulatory to comply with the government policy. It needs the cooperation among companies from being charged business model with the existence of promos for insurance participants or potential participants so that people recognize and be interested, invite to all society levels of the insurance importance in life to reduce any risk that might occur and to invite all people participating in fintech innovation.Keywords: Analytic Network Process, islamic insurance, fintech